A meta-analysis of levetiracetam for randomized placebo-controlled trials in patients with refractory epilepsy - Chen D (Dove Medical Press, 2019)
Daye Chen, Hongliang Bian, Lanlan Zhang Department of Pediatrics, Yancheng Maternal and Child Health Hospital, Yancheng, People’s Republic of China Objective: The objective of this study was to investigate the efficacy and safety profile of levetiracetam as add-on therapy in patients with refractory epilepsy.Methods: Web of Science, MEDLINE (Ovid and PubMed), Cochrane Library, EMBASE, and Google Scholar were systematically searched to identify potential eligible randomized controlled trials by two reviewers independently. Pooled estimates of risk ratios (RRs) for 50%, 75%, and 100% reduction from baseline were calculated using the fixed-effect model or random-effect model. Quality of included studies was assessed with the Cochrane Collaboration’s Risk of Bias tool. Serious adverse events and withdrawals induced by interventions and the most common side effects were analyzed.Results: Seventeen trials with a total of 3,205 participants were included in this meta-analysis, including 14 trials for adulthood and three trials for children. Pooled estimates suggested that levetiracetam was an effective anti-epileptic drug at 1,000–3,000 mg/day (RR =2.00 for 1,000 mg/day, RR =2.68 for 2,000 mg/day, RR =2.18 for 3,000 mg/day) for adults and 60 mg/kg/day (RR =2.00) for children compared to placebo in terms of 50% reduction from baseline. Likewise, as for seizure freedom rate, levetiracetam had an advantage over placebo at 1,000–3,000 mg/day (RR =5.84 for 1,000 mg/day, RR =4.55 for 2,000 mg/day, RR =4.57 for 3,000 mg/day, respectively) for adults and 60 mg/kg/day (RR =4.52) for children. Regarding safety profile, patients treated with levetiracetam had significantly higher occurrence than placebo for somnolence, asthenia, dizziness, infection, nasopharyngitis, anxiety, and irritability; however, most studies reported that these adverse events were mild and transient.Conclusion: Levetiracetam is an effective anti-epileptic drug for both adults and children with generalized or partial-onset refractory seizures at 1,000–3,000 or 60 mg/kg/day, with a favorable adverse event profile. Keywords: levetiracetam, adjunctive, refractory epilepsy, placebo